INCREASING THE QUALITY OF LIFE FOR THE ELDERLY THROUGH THE IMPLEMENTATION OF A CLEAN AND HEALTHY LIFE PATTERN (PHBS) AT THE ELDERLY INTEGRATED SERVICE POST (POSYANDU), 26 ILIR DISTRICT, PALEMBANG - Erman, Imelda; Azwaldi, Azwaldi; Damanik, Hanna; Agustin, Ismar (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
In Southeast Asia, the elderly population is 8% or around 142 million people. In 2000 the number of elderly people was around 5,300,000 (7.4%) of the total population, while in 2010 the number of elderly people was 24,000,000 (9.77%) of the total population, and in 2020 it is estimated that the number of elderly people will reach 28,800,000 (11.34%) of the total population. . While in Indonesia alone in 2020 it is estimated that the number of elderly people is around 80,000,000. In old age, a person will experience changes in terms of physical, cognitive, and psychosocial life. also emphasized the importance of life expectancy and quality of life for the elderly. Ratna (2008) also added that if these needs are not met, problems will arise in the life of the elderly which will reduce their quality of life. Kelurahan 26 Ilir, Bukit Kecil District, located in Palembang City, is estimated to have a fairly large elderly population. The first problem is that the elderly do not have sufficient knowledge about the quality of life in the elderly. The second problem that needs attention is the physical condition of the elderly. Physical health is an integral part of sports activities. For this reason, it is necessary to educate the elderly about the quality of life in the elderly and the ways that can be done so that people can live in their old age with quality. This activity is carried out by conducting health education for the elderly. The second solution is that the elderly are given health education about how to do physical activities at home, such as light exercise at home and regular walking.